2019
DOI: 10.1101/520916
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chromatin interactome mapping at 139 independent breast cancer risk signals

Abstract: Genome-wide association studies have identified 196 high confidence independent signals associated with breast cancer susceptibility. Variants within these signals frequently fall in distal regulatory DNA elements that control gene expression. We designed a Capture Hi-C array to enrich for chromatin interactions between the credible causal variants and target genes in six human mammary epithelial and breast cancer cell lines. We show that interacting regions are enriched for open chromatin, histone marks for a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
3

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…Therefore, we speculated that CCVs may also act distally through regulatory elements that interact with mencRNA promoters. Using Capture Hi-C data from breast cells [10], we identified 770 mencRNA promoters (defined as ± 500 bp from the transcription start site) that looped to a region containing a CCV (Additional file 2: Tables S11 and S14). For example, at 16q12.2, CCV rs11642015 is an eVariant (p < 5 × 10 −4 ) for the mencRNA XLOC-093918, with the risk haplotype associated with increased XLOC-093918 levels ( Fig.…”
Section: Evidence For Distal Ccvs Modulating Mencrnasmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, we speculated that CCVs may also act distally through regulatory elements that interact with mencRNA promoters. Using Capture Hi-C data from breast cells [10], we identified 770 mencRNA promoters (defined as ± 500 bp from the transcription start site) that looped to a region containing a CCV (Additional file 2: Tables S11 and S14). For example, at 16q12.2, CCV rs11642015 is an eVariant (p < 5 × 10 −4 ) for the mencRNA XLOC-093918, with the risk haplotype associated with increased XLOC-093918 levels ( Fig.…”
Section: Evidence For Distal Ccvs Modulating Mencrnasmentioning
confidence: 99%
“…We have recently shown that CCVs are enriched in genomic features associated with regulatory activity in a range of breast-derived cell lines including sites of open chromatin, chromatin marks associated with promoter and enhancer activity (H3K4Me3, H3K4Me1, and H3K27Ac), and transcription factor binding sites [9,10]. Capture Hi-C analyses have identified annotated gene promoters that frequently interact with these CCV-containing elements providing a list of candidate risk genes for these signals [10]. However, at 20 signals, we found no evidence of CCVs falling in regions marked by regulatory activity suggesting that some signals alter risk through alternative mechanisms [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At six AEI-identified genes (CASP8, GATAD2A, HSPA4, KLHDC7A, LGR6 and ZC3H11A), breast cancer CCVs are located in the promoter regions, suggesting the CCVs may confer allelic imbalance through altered promoter activity. Moreover, for six genes (BARX2, GATAD2A, HSPA4, LGR6, NTN4 and ZC3H11A), our recent capture Hi-C data has indicated that chromatin looping occurs between a region containing the breast cancer CCVs and the promoter of the corresponding gene 11 .…”
Section: Breast Cancer Ccvs Distally Regulate the Aei Gene Ntn4mentioning
confidence: 91%
“…Twenty-three target genes in 14 regions were predicted with high confidence (designated "Level 1"), of which 22 target genes in 13 regions were predicted to be distally regulated. These targets include four genes predicted as INQUISIT targets in previous studies 12,13 POLR3C, RNF115, SOX4 and TBX3, a known somatic breast cancer driver gene 14 , and genes implicated by transcriptome-wide association studies (LINC00886 15 and YBEY 16 ).…”
Section: Supplemental Figures 8-9mentioning
confidence: 99%